The dynamics of international migration and settlement in Europe a state of the art - Penninx, Rinus 1948-; Berger, Maria 1974-; Kraal, Karen ca. 20./21. Jh (Amsterdam University Press, 2006)
Between 1991 and 2001, the size of Britain's ethnic minority population increased by a full fifty percent. In that same decade, approximately one million immigrants settled in Britain. Similar patterns of migration and settlement are taking place in other European countries, such as Germany and France. The Dynamics of Migration and Settlement in Europe explores the causes and consequences of such massive changes in demography. Researchers at the IMISCOE-Network of Excellence (Immigration, Integration and Social Cohesion in Europe) bring together a wealth of theoretical and analytical research in this collection of essays addressing the many crucial questions that have arisen in the past two decades. Underlying these essays is a key concern for the healthy management of these new migration processes, as well as the eventual shape of the new societies that are just beginning to emerge. International migration and the ensuing questions about integration continue to be subjects of intense debate, and this book will be welcomed among those involved in migration studies and international development